2001
DOI: 10.1128/aac.45.4.1151-1161.2001
|View full text |Cite|
|
Sign up to set email alerts
|

Novel Carbapenem-Hydrolyzing β-Lactamase, KPC-1, from a Carbapenem-Resistant Strain ofKlebsiella pneumoniae

Abstract: A Klebsiella pneumoniae isolate showing moderate to high-level imipenem and meropenem resistance was investigated. The MICs of both drugs were 16 g/ml. The ␤-lactamase activity against imipenem and meropenem was inhibited in the presence of clavulanic acid. The strain was also resistant to extended-spectrum cephalosporins and aztreonam. Isoelectric focusing studies demonstrated three ␤-lactamases, with pIs of 7.2 (SHV-29), 6.7 (KPC-1), and 5.4 (TEM-1). The presence of bla SHV and bla TEM genes was confirmed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
754
2
43

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,444 publications
(809 citation statements)
references
References 65 publications
(73 reference statements)
10
754
2
43
Order By: Relevance
“…La presencia del gen bla KPC se determinó por medio de PCR según el protocolo de Yigit, et al (16). Se preparó una suspensión de una colonia en agua ultrapura y se usó 1 µl como plantilla para la reacción de PCR.…”
Section: Procedimientosunclassified
See 1 more Smart Citation
“…La presencia del gen bla KPC se determinó por medio de PCR según el protocolo de Yigit, et al (16). Se preparó una suspensión de una colonia en agua ultrapura y se usó 1 µl como plantilla para la reacción de PCR.…”
Section: Procedimientosunclassified
“…Desde su primera detección en Klebsiella pneumoniae en 1996 (16), las KPC se han reportado como causantes de epidemias dentro y fuera de Estados Unidos (17)(18)(19)(20)(21)(22)(23). En Colombia, el primer reporte de una KPC se hizo en K. pneumoniae en 2006 (14) y en 2007 se reportó por primera vez en el mundo en Pseudomonas aeruginosa (17).…”
unclassified
“…pneumoniae possessing bla KPC-2 and E. coli with the pBR322-catI-bla KPC-2 plasmid were a kind gift from Dr. Fred Tenover from the Centers for Disease Control and Prevention, Atlanta, GA. 9 The cloning of bla KPC-2 into pBC SK (þ) phagemid (Stratagene, La Jolla, CA) and into pET24a(þ) plasmid (Novagen, Darmstadt, Germany) is previously described. 14 WT and Trp105 variants of pBR322-catI-bla KPC-2 and pBC SK (þ) bla KPC-2 were expressed in E. coli DH10B cells (Invitrogen, Carlsbad, CA).…”
Section: Bacterial Strains and Plasmidsmentioning
confidence: 99%
“…5,7,8 KPC-2 manifests a very broad substrate profile including penicillins, extended-spectrum cephalosporins, cephamycins, and carbapenems. 9,10 Moreover, Papp-Wallace et al showed that this enzyme is resistant to b-lactamase inhibitors (clavulanic acid, sulbactam, and tazobactam), which are typically given in combination with a b-lactam for the treatment of infections caused by b-lactamase producing pathogens. 11 Understanding the structural requirements that allow for this broad spectrum is critical for future b-lactam and b-lactamase inhibitor design.…”
Section: Introductionmentioning
confidence: 99%
“…Klebsiella pneumoniae carbapenemase (KPC)-type enzymes were fi rst reported in carbapenem-resistant K. pneumoniae strains in North Carolina, United States (1) . Until 2005, the geographical distribution of these enzymes in members of the family Enterobacteriaceae -K. pneumoniae, in particular -was limited to the eastern part of the United States.…”
mentioning
confidence: 99%